Peningkatan Kesadaran Jemaat Dalam Pemberian Persepuluhan Melalui Pembinaan Mental Spiritual Keluarga (Studi Kasus : Di Gereja Pentakosta Indonesia Sidang Aek Habil Sibolga) - ASIDO GABE PARUNTUNGAN PASARIBU (Jurnal Euangelion, 2021)
It should be said that the indicator of spirituality is commitment to tithe, so members of the Indonesian Pentecostal Church congregation at the Aek Habil congregation are not included in this indicator, because of the lack of awareness to tithe. For this reason, the research was carried out to determine the cause of the congregation's lack of awareness to give. The method used in this research is qualitative research methods with case studies using tools such as interviews, questionnaires, and documentation. The results of the study contained detailed data on the congregation, in order to obtain a conclusion based on the congregation's information. Visits to church homes and providing mental formation through spiritual activities can increase the congregation's awareness of tithing. Key words: Increased awareness, tithe giving, spiritual mental building